Risk Analysis of Indonesian Mango Sustainable Supply Chain For Singapore Market - Maulida, Dwi Laila; Dwi Retno Andriani (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2022)
UD WN Mango Sultan, Gresik succeeded in exporting 1 ton of mangoes to Singapore in 2021. However, exports are still not sustainable because they are constrained by several risks faced in the mango supply chain. To support the development of mango sales, it is inseparable from good and sustainable supply chain management. Good supply chain management can reduce or anticipate the risks that are often faced by every supply chain actor. To reduce the impact of emerging risks, it is necessary to identify priority risks for further risk mitigation actions. This study aims to identify risks seen from the perception of each sustainable supply chain actor and evaluate the highest priority risk of each sustainable supply chain actor in mango commodities. The study uses primary data by conducting interviews and filling out questionnaires by informants from businessmen, farmers, and collector of mango commodity in Gresik District. Fuzzy Failure Mode and Effect Analysis (FFMEA) technique is used to determine the priority of risk mitigation efforts. The results show that there are 16 risk components for UD WN Mango Sultan and collectors, and 11 risk components for farmers. Meanwhile, the priority risks for farmers, collectors, and UD WN Mango Sultan are operational risk (5,355), social risk (7,414), and environmental risk (7,917).